Reassessing Attention to Fintech: Spillover Effects on Conventional and Islamic Financial Stocks - Ahmad Al Izham Izadin; Ooi Kok Loang; Mohd Shahidan Shaari; Abdul Rahim Ridzuan; Sevenpri Candra (Journal of Islamic Monetary Economics and Finance, 2026)
This study applies an integrated Quantile Vector Autoregression and Quantile Regression to examine spillover dynamics in the FinTech context. By analysing the period from 2019 to 2024, which includes significant events such as the COVID-19 pandemic, the 2023 banking crisis, and notable regulatory developments, the study captures nonlinear and asymmetric relationships between FinTech attention (ATFIN), FinTech stock performance (FINTS), and financial stock returns, for both conventional (FINS) and Islamic (IFINS) stocks. The findings suggest that ATFIN tends to respond to market movements during normal and bearish conditions, while it becomes a net transmitter during bullish periods, amplifying investor sentiment and speculative activity. Conventional financial stocks consistently emerge as strong transmitters of market spillovers, whereas Islamic financial stocks function mainly as receivers, especially during market upswings, indicating their potential role as a stabilizing force. These results contribute to the literature on behavioural finance and financial contagion by highlighting the asymmetric behaviour of FinTech attention across market regimes. The study also offers practical implications for regulators and institutional investors. Monitoring ATFIN may help identify speculative trends, while Islamic FinTech models could appeal to more risk-averse investment profiles.